Modelling on the Lithium - ion battery and its charging system used in aircraft - Xu, Nuo (2015)
As a result of low carbon concept has been proposed and publicize due to environmental concern, technologies that emit less greenhouse gas are more preferred. One of the efficient solution is to use more electricity to cut down the need to fossil fuel. A typical example is the trend of more electrical power in the modern aircrafts. This paper focuses the on the study of Lithium ion battery, which serves as an emergency power supply in the aircrafts. To improve the efficiency and reliability of the battery system, some challenges that related have to be recognized. Those includes estimation of state of charge, proposal of precise charging algorithm, selection of suitable topology and designing of accurate control technique. To deal with the above challenges, a phase shift zero voltage switching full bridge DC/DC converter is designed as the charger. Working principle and components parameters are explained in great details. In order to achieve constant current and constant voltage charging, a voltage mode controller is selected for the application. Finally, the charging processing is modeled and simulated. Simulation have covered under different loading and current. Results are verified and evaluated.